2016
DOI: 10.1089/end.2015.0691
|View full text |Cite
|
Sign up to set email alerts
|

Ring Suture Technique in Retroperitoneal Laparoscopic Partial Nephrectomy for Hilar Cancer: A New Renorrhaphy Technique

Abstract: The ring suture technique is safe and effective for management of renal hilar cancer during RLPN for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Therefore, it often takes more time for tumor excision and renorrhaphy, which is most intuitively shown by longer operation time, greater WIT and blood loss.There's study indicate that hilar tumor is the independent predictor for WIT [2]. With the development of medical equipment and improvement of surgical skill, the mean WIT of most studies has been limited in 30 mins (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) [2,3,13],an acceptable range. In the present study, there's no difference concerning the operation time, WIT, intraoperative blood loss and complication rate between two groups,and mean WIT in hilar tumor group is 19.8 mins,close to the result of RLPN [3].Our result has con rmed the safety and feasibility of 3DLPN for renal hilar tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it often takes more time for tumor excision and renorrhaphy, which is most intuitively shown by longer operation time, greater WIT and blood loss.There's study indicate that hilar tumor is the independent predictor for WIT [2]. With the development of medical equipment and improvement of surgical skill, the mean WIT of most studies has been limited in 30 mins (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) [2,3,13],an acceptable range. In the present study, there's no difference concerning the operation time, WIT, intraoperative blood loss and complication rate between two groups,and mean WIT in hilar tumor group is 19.8 mins,close to the result of RLPN [3].Our result has con rmed the safety and feasibility of 3DLPN for renal hilar tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We have also reported that self-retaining barbed suture method can improve suture e ciency and shorten WIT. For renal parenchymal reconstruction with hilar tumor, new technologies such as "V-hilar suture technique" [17] and "ring suture technique" [18] have been reported, and good clinical results have been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was placed in the full lateral decubitus position with overextension under general anesthesia. RLRN was performed using a standard 3-port technique by experienced surgeons, as previously described [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…After induction of general anesthesia, patients were placed in our modified lateral decubitus position [13]. The distribution of the ports was similar to that previously described by us [14]. The first port was placed through a 2 cm transverse incision located 2 cm below the tip of the twelfth rib and the retroperitoneal space was bluntly created with a handmade balloon dilator.…”
Section: Methodsmentioning
confidence: 99%